Women inheritance as a paradigm of the intersection between modernity and tradition in Francis Imbuga's Aminata - Majeed, Abdulhameed A.; Kaur, Hardev; Abdul, Zanyar Kareem (The University of Jordan, 2021)
This paper explores women inheritance as a cultural paradigm of the intersection between modernity and tradition in Francis Imbuga’s Aminata. It pinpoints such intersection through the lens of post-colonialism. The Kenyan native tradition is influenced by the British imperial modernity. Therefore, it demonstrates the cultural dichotomy between modernity and traditions because the natives reject any foreign interference in their cultural affairs, which is not sufficiently tackled in previous studies. The native characters’ opposition to women inheritance will be scrutinized to unravel Imbuga’s depiction of the natives’ rejection of the colonizers’ modernity. The interpretation of tradition is going to be pursued as a derisory response to the postcolonial persecutory culture regarding women inheritance in the aboriginal Kenyan society. By opposing the postcolonial modernity, the native Kenyans could preserve their ancestors’ cultural traditions i.e., their cultural identity is empowered by hindering women inheritance. The play approaches common themes regarding modernity and tradition; and it deals with the Kenyan aboriginal nations that were formed according to British cultural imperialism. As such, Imbuga offers a new literary insight on the drastic cultural changes in Kenyan in the ensuing years of post-colonialism. The study unravels his perception of the natives’ rejection of the postcolonial modernity in order to accentuate the supremacy of the native traditions over the foreign culture. Thus, the significance of the study lies in its original reading of modernity and tradition and how they enhance the Kenyan natives’ reaction to the emergence of women inheritance in their society.